REFORMULASI PERLINDUNGAN HUKUM PEKERJA GIG ECONOMY BERDASARKAN UNDANG-UNDANG NOMOR 6 TAHUN 2023 TENTANG CIPTA KERJA - Nur Syahdila; Diana Fitriana; Sri Wahyuni (Truth de Journal, 2026)
The development of the digital economy has given birth to a new model of employment relations through the gig economy system that offers flexibility for workers and digital platform companies. However, the pattern of legal relations that place workers as partners causes the non-fulfillment of various normative rights that have been inherent to workers, such as the right to a decent wage, social security, and occupational safety protection. This study aims to analyze the construction of legal relations between digital platform companies and gig economy workers and formulate a reformulation of legal protection arrangements that are able to provide legal certainty without having to classify gig economy workers as conventional workers. This research uses normative legal research methods with a legislative approach, a conceptual approach, and a comparative approach. Legal materials are obtained through literature studies that are analyzed descriptively-analytically. The results of the study show that employment regulations in Indonesia, especially Law Number 6 of 2023 concerning Job Creation, have not accommodated the characteristics of digital platform-based employment relationships, thus creating a legal vacuum for the status of gig economy workers. Seeing this urgency, it is necessary to reformulate regulations through the establishment of a special legal category for platform workers who are able to maintain work flexibility while guaranteeing basic rights in the form of wage protection, social security, and job safety.